Characteristics of the Nafion (R) - impregnated polycarbonate composite membranes for PEMFCs - Kim, KH; Ahn, SY; Oh, IH; Ha, HY; Hong, SA; Kim, MS; Lee, Y; Lee, YC (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
In this work, polycarbonate composite membranes were prepared for proton exchange membrane fuel cells (PEMFCs). In the preparation of membranes, a small amount of poly(ethylene glycol) (PEG) was blended with polycarbonate (PC) solution and then cast to make membranes. PEG contained in the membrane was removed by the high solubility of supercritical CO2 to afford porosity in the membrane. Then, porous PC membranes were soaked in Nation((R)) solution to yield the PC/Nafion((R)) composite membranes. The PC composite membrane had lower ion conductivity but higher conductance than Nafion((R)). (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: ELECTROLYTE MEMBRANES; PHASE-SEPARATION; FUEL-CELLS